Strategi Ketahanan Tanpa Akhir Di Era Persaingan Tranformasi Digital (Studi Kasus Percetakan Raffaeza) - Deri Deri; Suwarni Suwarni; Ahmad Soleh (Utami Publisher, 2026)
The development of digital technology has brought significant changes to business models in various sectors, including the printing industry. Increasingly fierce competition has forced businesses to adapt to innovation and sustainable strategies. This study aims to analyse the endless resilience strategy implemented by Raffaeza Printing in facing the challenges of digital transformation. This study uses a qualitative method with a case study approach. Data was obtained through observation, in-depth interviews, and documentation. The results show that Raffaeza was able to survive through three main strategies, namely (1) digitisation of customer services, (2) diversification of technology-based products, and (3) strengthening human resources through digital training. These strategies have proven effective in improving operational efficiency, expanding the market, and maintaining customer loyalty. This study emphasises the importance of continuous innovation and technological adaptation as the foundation of business resilience in the digital era.